2005
DOI: 10.1111/j.1365-2966.2004.08470.x
|View full text |Cite
|
Sign up to set email alerts
|

Starbursts and the triggering of the activity in nearby powerful radio galaxies

Abstract: We present high‐quality long‐slit spectra for three nearby powerful radio galaxies – 3C 293, 3C 305 and PKS 1345+12. These were taken with the aim of characterizing the young stellar populations (YSP), and thereby investigating the evolution of the host galaxies, as well as the events that triggered the activity. Isochrone spectral synthesis modelling of the wide wavelength coverage spectra of nuclear and off‐nuclear continuum‐emitting regions have been used to estimate the ages, masses and luminosities of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
184
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(217 citation statements)
references
References 67 publications
(123 reference statements)
29
184
4
Order By: Relevance
“…We note that this is more than a factor 10 greater than the upper limit on the current star-formation rate of ≤0.07 M yr −1 estimated from the infrared emission. For 3C 293 we find a significantly more complex starformation history (see also Tadhunter et al 2005). Namely ∼80% of the stellar mass of 3C 293 was formed at high redshift, ∼20% were formed in a more recent star-formation episode about 1−2 × 10 9 yrs ago , found similar results).…”
Section: Differing Star-formation Histories: Cluessupporting
confidence: 70%
“…We note that this is more than a factor 10 greater than the upper limit on the current star-formation rate of ≤0.07 M yr −1 estimated from the infrared emission. For 3C 293 we find a significantly more complex starformation history (see also Tadhunter et al 2005). Namely ∼80% of the stellar mass of 3C 293 was formed at high redshift, ∼20% were formed in a more recent star-formation episode about 1−2 × 10 9 yrs ago , found similar results).…”
Section: Differing Star-formation Histories: Cluessupporting
confidence: 70%
“…From two-dimensional fitting of a wellmatched sample of 33 AGNs (radio-loud and radio-quiet QSOs, as well as radio galaxies), using images obtained with the Wide Field and Planetary Camera 2 (WFPC2) on board HST, D03 concluded that ''for nuclear luminosities M V < À23:5, the hosts of both radio-loud and radio-quiet AGNs are virtually all massive elliptical galaxies with basic properties that are indistinguishable from those of quiescent, evolved, low-redshift ellipticals of comparable mass.'' Such conclusions conflict with recent findings of significant amounts of dust and cold molecular gas, as well as young stellar populations, in many radio-loud and radio-quiet QSOs (e.g., Martel et al 1999;Canalizo & Stockton 2001;Evans et al 2001;Scoville et al 2003;Tadhunter et al 2005;Barthel 2006). Although the hosts of most luminous AGNs are bulge-dominated, they seem to be significantly bluer than inactive elliptical galaxies, and indeed show evidence for starbursts in the relatively recent past (1-2 Gyr; e.g., Kauffmann et al 2003;Sánchez et al 2004;Canalizo et al 2006;Schweitzer et al 2006;Jahnke et al 2007).…”
Section: Introductioncontrasting
confidence: 71%
“…This peak suggests that there has been enhanced star formation due to a merger event, which implies a time delay of 1−3 Gyr between the peak of starburst activity and the end of the merger. This timescale agrees with the time delay of ∼2 Gyr found by hydrodynamical simulations of galaxy mergers (Lotz et al 2008), and with the timescales of 0.5−2 Gyr found observationally for individual objects (e.g., Tadhunter et al 2005;Emonts et al 2006). On the other hand, the jet dynamic age of 10 6 yrs derived for the X-shaped sources also agrees with the time delay between the merger event and the onset of the radio-AGN triggered activity found by other studies to be 10 6 years (e.g., Emonts et al 2006).…”
Section: Discussionsupporting
confidence: 90%